Morphological Changes on the Interventricular Septal Myocardium within the First Hours after Alcohol Septal Ablation in Patients with Hypertrophic Cardiomyopathy - V. P. Zakharova; K. V. Rudenko; L. O. Nevmerzhytska; A. A. Balabai; S. I. Dorofeeva; O. S. Chumak (Ukrainian Journal of Cardiovascular Surgery, 2019)
ASA is an alternative treatment for HCM. The literature does not reflect myocardial changes in the first hours after ASA.Objective: to describe the data on the study of morphological changes in the myocardium of two patients with obstructive HCM one and ten hours after ASA.Patients: patient G., 55 years old, NYHA class III, pressure gradient in the LV outflow tract – 116 mm Hg, IVS thickness of 2.2 cm, mitral regurgitation – 35%. During ASA, bradycardia developed, what turned into asystole. Haemodynamics was restored. However, an hour later, recurrent asystole occurred, which led to death. Patient K., 66 years old, with clinical signs corresponding to NYHA class III, LV systolic pressure gradient – 49 mm Hg., IVS thickness – 2.4 cm, 28% mitral regurgitation. One hour after ASA, signs of hemodynamic deterioration appeared, which resulted in death in 10 hours. The autopsy showed that the cause of death was bleeding from the subclavian artery at the puncture site for the central venous catheter.Methods: macroscopy, microscopy of histological samples stained with hematoxylin and eosin, Van Gieson’s picro-fuchsin, Weigert’s fuchselin, by MSB method modified by Zerbino-Lukasevich.Results: In microvessels, there were changes in the walls associated with alcohol coagulation of their structures. The lumens of arteries and arterioles were occluded with “shadows” of red blood cells or with small blood clots, which caused ischemic damage to CMC. Alcohol leakage beyond the capillaries was accompanied with coagulation necrosis of the surrounding CMC. 10 hours after ASA, WBC infiltrates were present in the affected areas.